The Influence of Digital Marketing on the Development of MSMEs in Manado City Sulawesi Utara - Hendrawati Hamid; Chandra Putra Kusniadi (Indonesian Journal of Advanced Research, 2024)
The purpose of this study is to examine how digital marketing has impacted the growth of different MSMEs in Manado City. Digital marketing offers convenience to customers while solving marketing issues and making the process more effective and efficient. MSME development is a collection of initiatives aimed at bolstering the expansion of the business environment and supporting current companies so that small firms can grow into robust, self-sufficient, expanding, and sustainable enterprises. The methods used in this study are quantitative and descriptive. The Slovin formula and non-probability sampling techniques were used to select 125 business actor respondents from the 23,375 MSMEs that made up the study's population. Tests for validity, reliability, homogeneity, normalcy, linearity, simple linear regression analysis, t-tests, and correlation coefficients are some examples of data analysis techniques. The study's findings demonstrate that digital marketing has a major impact on MSMEs' growth in Manado City at the same time. It is known that digital marketing has a 54.5% influence on the growth of MSMEs in Manado City based on the correlation coefficient test. Advice for MSME participants: In order for their companies to grow and be sustainable, they should keep using digital marketing.